The Formulation and Characterization of Nimodipine Nanoparticles for the Enhancement of solubility and dissolution rate - Alhagiesa, Areej Wahhab; M. Ghareeb, Mowafaq (Iraqi Journal of Pharmaceutical Sciences, 2021)
Nimodipine (NMD) is a dihydropyridine calcium channel blocker useful for the prevention and treatment of delayed ischemic effects. It belongs to class ? drugs, which is characterized by low solubility and high permeability. This research aimed to prepare Nimodipine nanoparticles (NMD NPs) for the enhancement of solubility and dissolution rate. The formulation of nanoparticles was done by the solvent anti-solvent technique using either magnetic stirrer or bath sonicator for maintaining the motion of the antisolvent phase. Five different stabilizers were used to prepare NMD NPs( TPGS, Soluplus®, HPMC E5, PVP K90, and poloxamer 407). The selected formula F2, in which Soluplus has been utilized as a stabilizer, has a particle size (77 nm) and polydispersity index (PDI) (0.016). The formulas with the smallest particle size were freeze dried with the addition of 1 % w/w mannitol as cryoprotectant. The saturation solubility of NMD in the prepared nanoparticles was increased twenty four-folds, and the complete dissolution was achieved at 90 minutes compared with pure NMD, which reaches only 6%. The formation of hydrogen bonding between NMD and the polymer or the cryoprotectant, as confirmed by the FTIR study. In conclusion, the preparation of NMD as polymeric nanoparticles is a useful technique for enhancing the solubility and dissolution rate.